The Concept of Chinese Chan: Perspectives from Tóng Méng Zhǐ Guān（童蒙止观） - Zhen, Venerable Guan (Journal of International Buddhist Studies, 2020)
To what extent can the practice of Buddhist śamatha and vipaśyanā meditation be seen as “Chinese Chan”? This article takes the initiative to analyze a short yet classical Chinese Buddhist text, the Foundations for Developing Buddhist Tranquility (Śamatha) and Insight (Vipaśyanā) Meditation童蒙止观. It examines the Foundations’ relationship with the elements of ancient Chinese culture and tradition that impact the practice of śamatha and vipaśyanā meditation. By revealing the fact that the meditation practice presented by the Foundations adopts substantial elements from ancient Chinese culture and tradition, this article suggests that the concept of “Chinese Chan” is significant for understanding the practice of śamatha and vipaśyanā meditation insofar as Chinese context is concerned.